The Coming of the Son of Man and the Mission to Israel (Matt 10:23) - Löfstedt, Torsten (Svensk exegetisk årsbok, 2025)
In the mission discourse, in a verse unique to Matthew, Jesus tells the twelve, "When they persecute you in this town, flee to the next, for truly I tell you, you will not have finished going through all the towns of Israel before the Son of Man comes" (10:23). This verse seems to contradict the eschatological discourse in the same Gospel, where Jesus says: "And this good news of the kingdom will be proclaimed throughout the world, as a testimony to all the nations, and then the end will come" (24:14). The seeming contradiction between 10:23 and 24:14 may be readily resolved by separating the coming of the Son of Man referred to in the mission discourse (10:23) from the end (24:14). I briefly explain the exegetical grounds for separating these two events and then answer important objections that have been raised against this interpretation. These include the claims that the coming of the Son of Man has the same meaning everywhere in Matthew; that Matthew would not have included instructions regarding the mission to Israel if he believed that mission had come to an end; and that the disciples were not persecuted during Jesus' earthly ministry so the mission discourse cannot refer to Jesus’ disciples in the period before the resurrection.